2013
DOI: 10.4103/1319-2442.109589
|View full text |Cite
|
Sign up to set email alerts
|

Candida lung abscesses in a renal transplant recipient

Abstract: We herein report a renal allograft recipient five years post transplant who had bilateral lung abscesses. The abscess grew Candida tropicalis on bronchoalveolar lavage. The patient was administered amphotericin B, but succumbed to massive hemoptysis. The case highlights a fungal complication in renal transplant and need for early suspicion and prompt therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…A particular problem with fungal lung abscess patients is that they are difficult to distinguish clinically from patients with bacterial sepsis which leads to delay in diagnosis and delay in antifungal therapy. [4] Once candida infection is confirmed, species level identification is must for prediction of antifungal susceptibility. [9] C. tropicalis have moderate level fluconazole resistant hence other antifungal drugs like Amphotericin B or Voriconazole should be considered for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A particular problem with fungal lung abscess patients is that they are difficult to distinguish clinically from patients with bacterial sepsis which leads to delay in diagnosis and delay in antifungal therapy. [4] Once candida infection is confirmed, species level identification is must for prediction of antifungal susceptibility. [9] C. tropicalis have moderate level fluconazole resistant hence other antifungal drugs like Amphotericin B or Voriconazole should be considered for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[10] To our knowledge there are very few cases of lung abscesses due to candida infection. [4,11,12] Gupta A et al (2013) reported a case of 45 year immunosuppressed male patient with history of renal transplant 5 years back. Patient was diagnosed as having C. tropicalis lung abscess and started on Amphotericin B but the patient died due to complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tuberculosis (TB) has been reported in kidney transplant recipients as an infection with predominance in lungs. Lattes et al in an analysis of the characteristics of adult kidney recipients with TB infection reported a fatal case of hemoptysis developed during the first month of TB treatment [9]. Fungal infections have been associated with hemoptysis in renal transplant recipients.…”
Section: Infectionsmentioning
confidence: 99%